Method Use: Everyone is a Teacher Here Assisted Media Rolling Ball Games in Increasing Student's Interest in Learning History - Suhaila, Alla (Riwayat: Educational Journal of History and Humanities, 2022)
This Article aims to describe the process of using the everyone is a teacher here learning method assisted by the rolling ball games media in learning history for class XI IPA 3 students at SMA Negeri 1 Bandar Baru and to determine the response of students' using the everyone is a teacher learning method assisted by rolling ball games media. Based on the results of the study, it was found that the level of interest in learning history of students got a score of 80% of the percentage of 100% which was included in the good category and the results of the evaluation value based on the calculation of the percentage of 80% of students completed and 20% incomplete. Based on the description above, it proves that the use of the everyone is a teacher here learning method assisted by rolling ball games media increases interest in learning history for students in class XI IPA 3 SMA Negeri 1 Bandar Baru . Student responses to the use of the everyone is a teacher here learning method assisted by the rolling ball games media received a positive response, this was evidenced by the percentage of student responses which was worth 81.8%.